Hal-Hal Yang Ada Hubungan Dengan Kanker Prostat Pada Penderita di Beberapa Lokasi Di Wilayah Asia, Amerika dan Eropa Pada Periode Tahun 2014 Sampai Dengan Tahun 2021 - Ananda, Helda Resky; Sartika, Suriana Dwi; Thamrin, Rahmawati (Fakultas Kedokteran Universitas Bosowa, 2024)
Prostate cancer is a malignant disease of the urogenital system originating from the prostate organ that attacks men and almost all prostate cancers originate from glandular cells, known as prostate adenocarcinoma.The purpose of this study was to find out things that have to do with the occurrence of prostate cancer in men in several locations in Asia, America and Europe for the period 2014 to 2021.The research method is an analytical research by synthesizing the results obtained from nine scientific research journals with a case control design.The results of the nine studies analyzed showed that there are things that have a relationship with the occurrence of prostate cancer in several locations in the Asia-Africa region, namely there is a significant relationship between age (p value 0.000), family history (p value 0.037), smoking (p value 0.000), and there was no significant relationship between nutritional status (p value 0.701), alcohol history (p value 0.614) on the incidence of prostate cancer in men. The conclusion is that the incidence of prostate cancer in men in several locations in Asia, America and Europe for the period 2014 to 2021 has a significant relationship with age, family history and smoking, and has no significant relationship with nutritional status and alcohol history